The role of leaders in laboratory safety: With an example from industry - David R. Franz (Elsevier, 2019)
Infectious disease research, like any scientific enterprise, is dependent on technology, subject matter experts, hard work ...and engaged leadership. The pace of progress in research and development of vaccines, drugs, diagnostics or foundational knowledge is always more rapid when laboratory organizational cultures are collaborative and communication is open. Relationships of trust between individual scientists and with their leaders in an organization further fuel productivity. Laboratory safety is sometimes seen as just another administrative function, but that is far from the case. A focus on safety in an infectious disease laboratory not only protects the staff and the community around the lab; it also contributes to a healthy and vibrant organizational culture and even enhances productivity.